2016
DOI: 10.1155/2016/9013816
|View full text |Cite
|
Sign up to set email alerts
|

Severe Methemoglobinemia due to Sodium Nitrite Poisoning

Abstract: Case. We report a case of severe methemoglobinemia due to sodium nitrite poisoning. A 28-year-old man was brought to our emergency department because of transient loss of consciousness and cyanosis. He was immediately intubated and ventilated with 100% oxygen. A blood test revealed a methemoglobin level of 92.5%. Outcome. We treated the patient with gastric lavage, activated charcoal, and methylene blue (2 mg/kg) administered intravenously. Soon after receiving methylene blue, his cyanosis resolved and the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 7 publications
2
52
0
Order By: Relevance
“…Our previous work showed that erythrocytes treated with 5 mM NaNO 2 exhibit significant and quantifiable alterations in stress parameters at this concentration (Ansari et al, ). It has also been reported that accidental or intentional (suicidal) ingestion of sodium nitrite results in high MetHb levels (>50%) in blood of affected persons, similar to those obtained by us using 5 mM NaNO 2 (Chui et al, ; Katabami et al, ). Our results show for the first time that crocin significantly protected erythrocytes from NaNO 2 ‐induced cell damage and can be an effective agent in mitigating oxidative stress and other damaging effects of nitrite on human tissues.…”
Section: Introductionsupporting
confidence: 81%
“…Our previous work showed that erythrocytes treated with 5 mM NaNO 2 exhibit significant and quantifiable alterations in stress parameters at this concentration (Ansari et al, ). It has also been reported that accidental or intentional (suicidal) ingestion of sodium nitrite results in high MetHb levels (>50%) in blood of affected persons, similar to those obtained by us using 5 mM NaNO 2 (Chui et al, ; Katabami et al, ). Our results show for the first time that crocin significantly protected erythrocytes from NaNO 2 ‐induced cell damage and can be an effective agent in mitigating oxidative stress and other damaging effects of nitrite on human tissues.…”
Section: Introductionsupporting
confidence: 81%
“…Ozen et al [21] have reported degenerative changes in organs of nitrite-treated mice. Although chronic exposure of humans to low doses of nitrite is common world-wide, many cases of intentional or accidental exposure to high doses of nitrite have also been documented [22,23]. However, reports on the mechanistic details of nitrite-induced oxidative stress in mammals are lacking in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported cases of methemoglobinemia secondary to sodium nitrate ingestion include individuals inadvertently using sodium nitrate in place of table salt due to inappropriate or non-existent labeling [6][7][8]. Our patient survived after a MetHb level of 92.7% on co-oximetry, which is among the highest recorded MetHb levels [9,10]. Katabami et al describe a case of methemoglobinemia after intentional ingestion of sodium nitrite with a MetHb level of 92.5% [9].…”
Section: Discussionmentioning
confidence: 70%
“…Methemoglobinemia occurs when MetHb levels in the circulation are greater than 1.5%. Notably, sodium nitrite is a very similar substance to sodium nitrate, and may also cause methemoglobinemia; such toxicity is treated in a similar fashion [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%